STUDY OF THE COST OF FIREWORMS CONTROLLING USING THE FOGGING METHOD IN OIL PALM (Elaeis guineensis Jacq) PLANTATIONS AT PT. PERKEBUNAN NUSANTARA VI REGIONAL 1 KEBUN BANGUN - M. Raihan Akbar Mubarok; Febriana Roosmawati (RADJA PUBLIKA, 2026)
The attack of fireworms (Setothosea asigna) can reduce the production of fresh fruit bunches by 40–60%, so an effective, cost-effective control method is needed. This study aims to evaluate the cost of fireworm pest control using the fogging method on oil palm plantations at PT Perkebunan Nusantara IV Regional 1 Kebun Bangun. The study used a descriptive method, collecting primary field data and secondary data from the 2024 RKAP and department management reports. The fogging process included an attack census, solution preparation, and nighttime fogging. The results showed that the total area of fireworm pest attacks reached 139 hectares across 17 blocks. The peak of the attack occurred in March (60 hectares) and decreased through July (20 hectares), indicating the effectiveness of the fogging method in controlling fireworms. Overall, the total control cost amounted to IDR 40,195,772, or IDR 289,178/ha. The average cost of fogging materials was Rp118,335/ha, fuel Rp10,000/ha, and labor Rp27,750/ha. The largest cost component came from equipment (46.02%), followed by materials (44.38%) and labor (9.60%). Thus, the fogging method has proven effective in suppressing fireworm attacks and provides a cost overview that can be used as a basis for decision-making in pest management on oil palm plantations.